Dynamics of the interaction between body fluid and Ti cp: the influence of surface functionalization in the first stages of osseointegration - Nascimento, Rodney Marcelo Do [UNESP]; Carvalho, Vanessa Rafaela De [UNESP] (SBEB - Sociedade Brasileira de Engenharia Biomédica, 2014)
INTRODUCTION: Regenerative therapies using biomaterials require accurate information on interactions between the implanted material and the human body. To improve the process of bone regeneration it is necessary to obtain a better understanding of the influence of the surfaces on the early stages of osseointegration. This work aims to investigate the dynamic interaction between simulated body fluid (SBF) and titanium surfaces (Ti cp) immediately after their first contact. METHODS: Ti cp samples were passed through physicochemical treatments after immersion in acid solution, alkaline solution and solutions containing TiO2 and Ca2+, to obtain three different surfaces. These were characterized by electron microscopy and free energy estimates. The evaluation of the interaction with SBF was performed by measuring the dynamic contact angles after contacting the surfaces. RESULTS: The effects of SBF wettability were more significant on surfaces according to high energy estimates. A comparative analysis of the three types of surfaces showed that fluid spreading was greater in samples with greater polar components, indicating that the surface nature influences interactions in the early stages of osseointegration. CONCLUSION: The results indicate the influence of polar interactions in the dynamic wettability of the SBF. It is possible that these interactions can also influence cellular viability on surfaces. Based on these results, new experiments are being designed to improve the presented methodology as a tool for the evaluation of biomaterials without the need for in vivo experiments.
Keywords: Osseointegration; Body fluid; Wettability; Surface free energy